Waterfall Method Design for Implementing Medical Record Retention at Rafflesia Hospital, Bengkulu - Heltiani, Nofri; Arifin, Ismail; Ayu, Elisa; -, Khairunnisyah (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
e-Retention is beneficial in supporting the efficient retention of medical record files. Retention is carried out by filing staff by selecting medical record numbers on the shelves by looking at the date/month/year of the patient's last visit and whether they have not returned for treatment for more than 5 years. A common problem in hospitals is that retained medical record data is not recorded or archived in the retention book. Consequently, when the patient returns for treatment, filing staff require considerable time to trace the medical record files to ensure they receive medical care. This impacts patient satisfaction with medical record services. This study aims to design a waterfall method for implementing medical record retention. Primary data were obtained through observation using a qualitative descriptive study using the waterfall method, with four staff members as subjects. The data used in this study were checklists, which were then processed and analyzed univariately. The result of this research is a design for an e-retention system for medical record files that is ready for implementation. This implementation is expected to improve the efficiency and accuracy of e-retention. Suggestions include making changes to the implementation of medical record file retention to make it more effective by using e-retention, providing training to staff on its use, and conducting an impact evaluation to measure efficiency and patient satisfaction resulting from the system changes.